2020
DOI: 10.1055/a-1180-0111
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zu Einflussfaktoren auf die Influenza-Impfraten bei Patienten mit chronisch obstruktiver Lungenerkrankung

Abstract: Zusammenfassung Hintergrund Bei niedrigen Influenza-Impfraten unter chronisch Kranken sollen Ansätze zu deren Steigerung unter Risikopatienten mit chronisch obstruktiver Lungenerkrankung (COPD) aufgedeckt werden. Methoden 120 COPD-Patienten aus Magdeburg füllten einen Fragebogen mit selbst erstellten Fragen und etablierten Skalen aus und wurden bez. des Influenza-Impfstatus 2015/2016 bzw. 2016/2017 analysiert. Geimpfte und Ungeimpfte wurden in sozioepidemiologischen Faktoren, Komponenten de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(35 reference statements)
2
0
0
Order By: Relevance
“…Concerning influenza, we did not identify an association between mental health and vaccination readiness. This observation is in line with another German study concerning depression and vaccination behavior against influenza in adults with COPD [ 46 ]. Another German study concluded that the broader construct of anxiety showed no association with vaccine acceptance in a German convenience sample.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning influenza, we did not identify an association between mental health and vaccination readiness. This observation is in line with another German study concerning depression and vaccination behavior against influenza in adults with COPD [ 46 ]. Another German study concluded that the broader construct of anxiety showed no association with vaccine acceptance in a German convenience sample.…”
Section: Discussionsupporting
confidence: 92%
“…As already shown, a subjectively perceived high-quality doctor/patient relationship seems to have a strong positive association with vaccination readiness [24,25]. Furthermore, we confirmed that older age, the male sex, and higher education are associated with increased vaccination readiness in patients with chronic conditions [17,46,48]. The role of patient activation was ambivalent, being associated with higher scores for "confidence" and "calculation".…”
Section: Discussionsupporting
confidence: 85%